STEM literacy questionnaire as an instrument for STEM education research field: Development, implementation and utility - Suthida Chamrat (2019)
© 2019 Author(s). STEM and STEM education emphasize the transformative learning that brings each subject into the borderless and seamless "transdisciplinary" integration. This reflects the authentic incorporation of science, technology, engineering and mathematics in real life, which relates to society, economy and environment. However, the existing research instruments to measure STEM literacy normally reflect the SILO ideas since they are used to measure scientific literacy, technological literacy, engineering literacy and mathematical literacy separately. This research aims to fill the gap of STEM research field by developing STEM literacy instruments which focus on the integration of STEM. Reviewing the existing research and literature, 14 documents were found defining "STEM literacy". The content analysis by narrative systematics review was used in this study, indicated that the definition grounded into 5 categories: STEM concepts, STEM practices, STEM applications, STEM attitudes, and STEM related context. The process of STEM literacy Questionnaire as a research instrument was also presented along with the findings from 142 teachers who completed the questionnaire. The implication suggested the way to use it as STEM education filed research instrument and the possible future research that utilize it.